Making sense of big text: A visual-first approach for analysing text data using Leximancer and Discursis - Angus, Daniel; Rintel, Sean; Wiles, Janet (International Journal of Social Research Methodology, 2012)
This article reports on Leximancer and Discursis, two visual text analytic software tools developed at the University of Queensland. Both analyse spatial and temporal relationships in text data, but in complementary ways: Leximancer focuses on thematic analysis, while Discursis focuses on sequential analysis. Our report explains how they work, how to work with them and how visual concepts are relevant to all stages of their use in analytic decision-making.
Angus, D., Rintel, S. & Wiles, J. (2013). Making sense of big text: A visual-first approach for analysing text data using Leximancer and Discursis, International Journal of Social Research Methodology (Special Issue: Computational Social Science: Research Strategies, Design and Methods) 16 (3), 261-267